The racial violence and gender oppression: Palestinian womens struggle based on selected novels by Sahar Khalifah - Jasim, Iman Naemah (Tanjong Malim, 2022)
The racial violence and gender oppression: Palestinian womens struggle based on selected novels by Sahar Khalifah by Jasim, Iman Naemah